Characteristics of titanium dioxide nanotubes annealed under various conditions and quenched using liquid nitrogen. (16th July 2022) - Low, K.T.; Beh, K.P.; Lim, H.S.; Yam, F.K.
This paper presents the effects of the different annealing treatments and quenching conditions on the characteristics of titanium dioxide nanotubes (TNTs), which were synthesised successfully via two-step electrochemical anodisation. A novel approach was employed in this study by quenching annealed TNTs using liquid nitrogen (N2 ). The XRD results showed that TNTs annealed and quenched using liquid N2 exhibited dissimilarities in the phase transition and plane dominance compared to that of air quenched when annealed at 750°C. It also revealed that the liquid N2 quenching was capable of suppressing the phase transition of anatase into rutile when annealed at 750°C. Apart from that, different quenching methods were found to vary the crystallite size of anatase and rutile of the annealed TNTs, whereby L-series samples have larger anatase crystal and vice versa for that of W-series samples. FE-SEM images showed that the use of controllable water vapour/N2 was able to preserve the nanotubular structures, even at the high annealing temperature of 850°C. Despite having the same anodisation parameters, different quenching methods were found to modify the morphology of TNTs, particularly the pore size. On top of that, the study also disclosed that the dominant phase determined the close relationship between crystallite size and band gap energy in which smaller crystallite size could induce quantum confinement effect, subsequently influenced the band gap, particularly in mixed-phase structures.